Marketing Characteristics Through Social Media That Are Able To Produce Brand Equity And Consumer Response Through Consumer Interest - Bagus Kristanto Putra (Soegijapranata Catholic University, 2021)
The internet is not a strange thing in people's lives, now with the internet, it is easier for people to communicate between regions and between countries. Internet, which stands for inter and networking, is a collection of computer networks and various types that communicate with each other using a communication standard. The method used in this literature search is the systematic literature review (SLR) method. By using this method, researchers can carry out systematic reviews and journal identification in which each process follows the steps that have been determined. Based on the results of the review search for the article above, the researcher can conclude: (1) there are so many articles about the characteristics of good social media, and affect many factors so that researchers find many new problems that are interesting to research. (2) Some articles state that the main characteristics that must be owned are attractive and customization so that it can affect the brand equity of a brand.